Penerapan Komponen - Komponen Ekspositoris dalam Penyutradaraan Film Mokumenter “Dari Gadget ke Dinding Sepi” - Willy Andro Denelsen Tamba; Kokom Komariah; Fajar Syuderajat (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
The mockumentary film Dari Gadget ke Dinding Sepi explores the negative impact of gadget use on teenagers, particularly regarding exposure to pornographic content. This film was created as part of a community service initiative to raise awareness about the importance of technology supervision among youth. This study aims to explain the directing process using an expository approach through four main components: narration, visuals, data and facts, and structure. The method includes pre-production, production, and post-production stages, with data obtained through field observation and interviews with expert sources. The results show that the expository approach helps to build a logical, informative, and accessible storyline. This film is expected to serve as a communication tool that raises awareness of digital literacy and the impact of digital content on teenagers